The Effect of Think Pair Share Learning Model with the Help of Geogebra Software on Students' Mathematical Communication Skills - Khaq, Astafil; Wahid, Candra (International Journal of Research in Mathematics Education, 2023)
The background of this study is the lack of mathematical communication skills of students. Researchers chose the think pair share cooperative learning model with the help of geogebra software to overcome this students' lack of mathematical communication skills. The purpose of this study is to determine how the implementation and whether there is an influence of the think pair share cooperative learning model with the help of geogebra software on students' mathematical communication skills. This research is a type of quasi-experimental research (quasy experimental design) and the design used is the pretest-posttest control group design. The population of this study was 320 students of grade VIII MTs Negeri 1 Purbalingga. The research sample was 40 students of class VIII A as a control class and 39 students of class VIII B as an experimental class. Based on the analysis of observation sheet data, an average value of 3.38 was obtained and was located at intervals of 3.25 ≤ x ≤ 4.00 which was classified as very good. And based on the results of the t test against the post-test results that have been done, the value of Sig. 0.000 < 0.05 which means that there is an average difference in mathematical communication skills between the experimental class and the control class. The conclusion of this study is that the implementation of the think pair share learning model with the help of geogebra software is very good, so that it can affect the improvement of students' mathematical communication skills.